Accuracy of an Intimate Partner Violence Screening Tool for Female VHA Patients: A Replication and Extension. Issue 1 (26th January 2015) - Iverson, Katherine M.; King, Matthew W.; Gerber, Megan R.; Resick, Patricia A.; Kimerling, Rachel; Street, Amy E.; Vogt, Dawne
<x xml:space="preserve">Abstract</x> The 4‐item Hurt/Insult/Threaten/Scream (HITS) tool accurately detects past‐year intimate partner violence (IPV) among female Veterans Health Administration (VHA) patients; however, it lacks a sexual IPV item. This study evaluated the accuracy of an extended HITS (E‐HITS), which adds a sexual IPV item, in female VHA patients. A sample of 80 female U.S. veteran VHA patients in New England completed a mail survey (50.0% response rate) that included the 5‐item E‐HITS and the Revised Conflict Tactics Scales (CTS‐2). Women were included if they were in an intimate relationship in the past year. The women averaged 49 years of age and 86.0% of the sample was White. Accuracy of the 4‐item HITS was compared to the 5‐item E‐HITS, using the CTS‐2 as the reference. There were 20 women (25.0%) who reported past‐year IPV on the CTS‐2. The receiver operator characteristic curves demonstrated that the HITS and E‐HITS performed nearly identically at their optimal cutoff scores of 6 and 7, respectively. At these cutoff scores, the sensitivity of both tools was .75, 95% CI [.55, .95]. The specificities were similar; .83 for the HITS, 95% CI [.73, .92], and .82 for the E‐HITS, 95% CI [.72, .90]. Including a sexual IPV item may be clinically beneficial; it also attains the same accuracy of case identification as the HITS.